Enhancing Weighted Averaging for CNN Model Ensemble in Plant Diseases Image Classification - Octavian, Octavian; Badruzzaman, Ahmad; Muhammand Yusuf Ridho; Trisedya, Bayu Distiawan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
Deep learning, especially convolutional neural networks (CNN), has gained traction in the field of image classification. In the specific case of plant disease classification, improving the accuracy and reliability of image classification is paramount. This paper delves into the ensemble prediction technique using a weighted soft-voting method. Instead of assigning a generalized weight to each CNN model, our approach emphasizes giving weights to each label's prediction within every individual model. We employed three respected CNN architectures for our experiments: DenseNet201, InceptionV3, and Xception focus on classifying various diseases that affect grapes. By harnessing transfer learning coupled with end-to-end fine-tuning, we achieved a streamlined and efficient training process. In particular, the f1-score for each grape disease class was used as a parameter for weight determination and as a metric for the final evaluation. In our study, the newly proposed method was tested across various datasets and ensemble scenarios, demonstrating its effectiveness by not only outperforming the conventional soft-voting and prevalent weighted soft-voting methods, which achieved best scores of 95.68% and 95.81% respectively, but also by achieving a remarkable accuracy of 96.56%. The efficacy of this method is enhanced when the ensemble models exhibit distinct characteristics; the more varied the model characteristics, the more enhanced the ensemble results.